Focal therapy for prostate cancer: concepts and future directions. Issue 6 (November 2018) - Ashrafi, Akbar N.; Tafuri, Alessandro; Cacciamani, Giovanni E.; Park, Daniel; de Castro Abreu, Andre Luis; Gill, Inderbir S.
Abstract : Purpose of review: To present a perspective on the current status and future directions of focal therapy for prostate cancer (PCa). Recent findings: Focal therapy for localized PCa is a rapidly evolving field. Various recent concepts – the index lesion driving prognosis, the enhanced detection of clinically significant PCa using multiparametric MRI and targeted biopsy, improved risk-stratification using novel blood/tissue biomarkers, the recognition that reducing radical treatment-related morbidity (along with reducing pathologic progression) is a clinically meaningful end-point – have all led to a growing interest in focal therapy. Novel focal therapy modalities are being investigated, mostly in phase 1 and 2 studies. Recently, level I prospective randomized data comparing partial gland ablation with a standard-of-care treatment became available from one study. Recent developments in imaging, including 7-T MRI, functional imaging, radiomics and contrast-enhanced ultrasound show early promise. We also discuss emerging concepts in patient selection for focal therapy. Summary: PCa focal therapy has evolved considerably in the recent few years. Overall, these novel focal therapy treatments demonstrate safety and feasibility, low treatment-related toxicity and acceptable short-term and in some cases medium-term oncologic outcomes. As imaging techniques evolve, patient selection, detection of clinically significant PCa and noninvasive assessment of therapeutic efficacy will be further optimized. The aspirational goal of achieving oncologic control while reducing radical treatment-related morbidity will drive further innovation in the field.